Capital and popular cinema : The dollars are coming! - Vitali, Valentina (Book collections on Project MUSE., 2016)
Popular cinema has mostly been discussed from a 'cult' perspective that celebrates uncritically its 'transgressive' qualities. Capital and popular cinema responds to the need for a more solid academic approach by situating 'low' film genres in their economic and culturally-specific contexts and by exploring the interconnections between those contexts, the immediate industrial-financial interests sustaining the films, and the films' aesthetics. Through the examination of three different cycles in film production - the Italian giallo of Mario Bava, the Mexican films of Fernando Mňdez, and the Hindi horror cinema of the Ramsay Brothers - this book proposes a comparative approach that accounts for the whole of a national film industry's production ('popular' and 'canonic'), and is applicable to the study of film genres globally.